Acceleration of vessel‐selective dynamic MR Angiography by pseudocontinuous arterial spin labeling in combination with Acquisition of ConTRol and labEled images in the Same Shot (ACTRESS). Issue 5 (2nd December 2018) - Suzuki, Yuriko; Okell, Thomas W.; Fujima, Noriyuki; van Osch, Matthias J.P.
Abstract : Purpose: The recently introduced "Acquisition of ConTRol and labEled imaging in the Same Shot" (ACTRESS) approach was designed to halve the scan time of arterial spin labeling (ASL) ‐based 4D‐MRA by obtaining both labeled and control images in a single Look‐Locker readout. However, application for vessel‐selective labeling remains difficult. The aim of this study was to achieve a combination of ACTRESS and vessel‐selective labeling to halve the scan time of vessel‐selective 4D‐MRA. Methods: By Bloch equation simulations, Look‐Locker pseudocontinuous‐ASL (pCASL) was optimized to achieve constant static tissue signal across the multidelay readout, which is essential for the ACTRESS approach. Additionally, a new subtraction scheme was proposed to achieve visualization of the inflow phase even when labeled blood will have already arrived in the distal arteries during the first phase acquisition due to the long duration of the pCASL labeling module. In vivo studies were performed to investigate the signal variation of the static tissue, as well as to assess image quality of vessel‐selective 4D‐MRA with ACTRESS. Results: In in vivo studies, the mean signal variation of the static tissue was 8.98% over the Look‐Locker phases, thereby minimizing the elevation of background signal. This allowed visualization of peripheral arteries and slowly arriving arterial blood with image quality as good as conventional pCASL within half the acquisition time. Vessel‐selective pCASL‐ACTRESS enabled the separated visualization of vessels arising from internal and external carotid arteries within this shortened acquisition time. Conclusion: By combining vessel‐selective pCASL and ACTRESS approach, 4D‐MRA of a single targeted arterial tree was achieved in a few minutes.